Hashemite Kingdom of Jordan - Institutional Financial Management Capacity Assessment (IFMCA) : Education and Social Development Sectors - World Bank (Washington, DC, 2012)
During the past decade, the Government of Jordan implemented a full-fledged adjustment program with continuous support from the International Monetary Fund (IMF) and the World Bank. Economic growth during the last few years of the 1990s was over four percent, despite adverse external political factors. Gross Domestic Product (GDP) growth reached almost 5 percent in 2002, and was around 7 percent in 2004. Jordan graduated from the IMF program of support in July 2004. A World Bank report described Jordan as a star performer among emerging countries in terms of its structural reform achievements. In 2005, the government issued a ten-year strategic plan, the national agenda, which aimed to 'improve the quality of life of Jordanians through the creation of income-generating opportunities, the improvement of standards of living, and the guarantee of social welfare.' The plan set ambitious macroeconomic performance targets, to be achieved during the coming decade and clearly articulated performance measures to be used to monitor progress towards their achievement. The current Institutional Financial Management Capacity Assessment (IFMCA) selected two sectors the education and social development which are of importance to the Government of Jordan. Both sectors feature prominently in the government's recent national agenda and the Country Assistance Strategy (CAS). Both are being supported through a number of World Bank-supported projects and Economic Sector Works (ESWs).